2022
DOI: 10.3389/fpsyt.2022.990430
|View full text |Cite
|
Sign up to set email alerts
|

Association between temporomandibular disorders and anxiety: A systematic review

Abstract: Temporomandibular Joint Dysfunction (TMD) is an umbrella term that includes musculoskeletal and neuromuscular conditions affecting the temporomandibular joint. The present systematic review aimed to verify whether there is a specific association between TMD and anxiety. The searches were carried out in electronic databases, including PubMed, Scopus, Web of Science, and LILACS, without restrictions on publication date and language. The acronym PECO was used, whose participants (P) were humans exposed to TMD (E)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…As addressed above, in a similar context, a prospective study of female students before the university entrance reported a positive association between stress and TMD [ 7 ]. This positive association between stress and TMD was affirmed by a review of 33 original studies [ 8 ] and a survey of 112 participants in a general hospital [ 9 ]. This study extends the horizon of existing literature by employing explainable artificial intelligence and population data for identifying an association among PTB, TMD, GERD and antidepressant medication (depression) together.…”
Section: Discussionmentioning
confidence: 94%
“…As addressed above, in a similar context, a prospective study of female students before the university entrance reported a positive association between stress and TMD [ 7 ]. This positive association between stress and TMD was affirmed by a review of 33 original studies [ 8 ] and a survey of 112 participants in a general hospital [ 9 ]. This study extends the horizon of existing literature by employing explainable artificial intelligence and population data for identifying an association among PTB, TMD, GERD and antidepressant medication (depression) together.…”
Section: Discussionmentioning
confidence: 94%
“…TMD is considered to be related to psychosomatic factors such as anxiety, stress, and sleep disorders ( 17 , 18 ). Among them anxiety disorders are the most common of all mental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of TMD is still controversial. However, studies show that its origin is multifactorial, including biopsychosocial factors [ 7 , 8 ]. Risk factors that exert influence for a few years before the manifestation of TMD signs and symptoms (predisponents) must be taken into consideration, as well as those that act for the condition to develop (initiators) and those that cause the continuation of TMD (perpetuators), making it difficult for the outcome of the treatment [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%